Local Partnership as Mechanism to Create Wealth in Municipality in Algeria - Harizi, Zakaria; Bradcha, Farid (Journal of Social Sciences and Humanities, 2025)
Local partnership is a new model of local governance, including a set of mechanisms to create wealth in the municipal institutions in Algeria in order to improve the level and the degree of well-being of local citizens who are considered the center of this process, and for whom all development plans in the local sphere are constitutionally and legally adopted. Then, this new approach to local development has become necessary in the post-modern world for the State’s institutions work together to build and activate all partnership mechanisms among various local actors to create wealth, which remains the ultimate goal of all modernization and development programs.